Cesarean Scar Defect (Niche) Risk Factors: A Prospective Study on Indonesian Women - Lumbanraja, Irwin L.; Aldiansyah, Dudy; Halim, Binarwan; Lubis, Muara Panusunan; Kaban, Yostoto Berkat; Rivany, Riza (Current Women's Health Reviews, 2024)
Introduction: Niche or cesarean scar defect is a complication of a cesarean section that has long-term implications for both obstetrics and gynecology. The rate of niche is believed to be increasing with the high number of cesarean sections. This study assesses the risk factors for niche development after cesarean section. Methods: A prospective cohort study was conducted on women who underwent cesarean section at the Haji Adam Malik General Hospital Medan between August 2020 and August 2022. Niche was assessed six weeks after cesarean section using transvaginal ultrasonography. The primary outcome was the presence of a niche. The antepartum, intrapartum and postpartum risk factors were analyzed for niche development. A logistic regression model was used to assess independent risk factors from the bivariate analysis. Results: There were 280 patients enrolled in this study. The prevalence of niche was 44.3% by using transvaginal ultrasound. There was no significant relationship between maternal age, gestational age, parity, nutritional status based on upper arm circumference, hypertension in pregnancy, anemia status, surgical indications, duration of surgery, volume blood loss, and puerperal infection to niche development (P > 0.05). The independent risk factors for niche development were Cervical dilatation > 4 cm (P = 0.035; RR = 1.75), locking suture technique (P = 0.015; RR = 13.81), non-closure vesicouterine folds (P = 0.04; RR = 0.14) and a retroflexed uterus (P = 0.001; RR = 0.039). Conclusion: Cervical dilatation > 4 cm, locking suture technique, non-closure vesicouterine folds, and a retroflexed uterus are risk factors for niche development after CS.
Keywords: ultrasonography